Morphometric and meristic characteristics of the Amur sleeper (Perccottus glenii) from the Danube River drainage channel - Nikolić, Dušan; Skorić, Stefan; Cvijanović, Gorčin; Jaćimović, Milica; Đikanović, Vesna; Mićković, Branislav (Archives of Biological Sciences, 2021)
Paper description: The Amur sleeper, one of the most invasive alien fish species in Europe, has marked the 20th anniversary of its presence and spread in Serbia. The aim of this research was to better describe the body shape of this species in the Serbian part of the Danube River. Amur sleeper specimens were measured to describe its general body shape using the “point-to-point” method. A relatively low variability of morphometric and meristic characters was observed. The results presented herein contribute to a better understanding of the population characteristics of this species in Serbia. Abstract: In recent decades, the Amur sleeper (Perccottus glenii) is one of the most impressive east-to-west invaders of European inland waters, but there are insufficient data on its biology in the countries it has entered. Specimens of two sets of samples from November 2015 (n=25) and October 2016 (n=39) were caught in the Danube River channel near Veliko Gradište (Serbia) by electrofishing. Thirty morphometric and eight meristic characteristics of the collected fish were measured with the aim of describing the general body shape in more detail using the “point-to-point” method. This is the first attempt to obtain morphometric and meristic characteristics of Amur sleeper caught in Serbia. The results revealed a relatively low variability in the morphometric and meristic characters of the studied population. When compared to other studies, there was a great variability of the studied characteristics between geographically distant European populations that inhabit different water body types. Female fish had more robust bodies compared to males of the same length, while males had longer pectoral, anal and dorsal fins. Additionally, 2+ individuals had more robust heads and jaws, as well as longer anterior parts of the body compared to 1+ individuals of the same size.